170 The effects of supplementing a chelated mineral containing Ascophyllum nodosum on intake and performance of creep-fed hair lambs. (28th November 2020) - Romo, Victoria; Boyd, Jamie A
Abstract: The objective of this study was to determine the effect of two commercial mineral supplements on ewes/lamb pairs DMI and ADG. All ewes prior to lambing were maintained a sheep pellet formulated for no mineral, vitamin, or probiotic content at a rate of 2% body weight, ad libitum Bermuda hay, and ad libitum access to the control mineral supplement. Ewe/lamb pairs were randomly assigned based on twining and parity to study groups four days post-lambing. The treatment (TRT) group had 12 ewes/18 lambs, and a control (CNTRL) group had 11 ewes/17 lambs, and was conducted over 6wks. Lambs in both groups were offered ad libitum alfalfa via a creep feeding gate. The TRT group received a commercial chelated mineral mix that included Ascophyllum nodosum seaweed extract in the blend and the CNTRL received a commercial non-chelated mineral without seaweed extract. Chelated minerals were Cu, Mn, and Zn. Daily feed and ort samples were collected 2x week and dried at 55℃ for analysis. Feed was adjusted daily to maintain a 3–5% refusal rate. Samples were compiled by week and analyzed for DM, Ash, aNDF, aADF, EE, and CP. Blood samples were collected from a subset of 7 ewes per group, 3x during the study (wk1, wk3, wk6) for later trace mineral analysis (Co, Cu, Fe, Mn, Mo, Se). Results indicate a significant difference in mineral DMI between groups (P = 0.03), but no significant impact on DMI of Bermuda or alfalfa. ADG for lambs was numerically increased 0.25±0.01 TRT versus 0.23±0.01 kg CNTRL but was not statistically significant (P = 0.18). No significant differences in trace mineral levels between groups or over time was seen. All mineral levels were in the normal range for both groups. It appears the addition of the chelated mineral with Ascophyllum nodosum seaweed extract did not improve ADG or DMI, but the results of this study were potentially affected by severe weather conditions. Further study is needed under more favorable conditions to confirm product impacts in ewe/lamb pairs.